Orexins (hypocretins) and energy balance: More than feeding. (15th December 2015) - Fernø, Johan; Señarís, Rosa; Diéguez, Carlos; Tena-Sempere, Manuel; López, Miguel
Abstract: Initially implicated in the regulation of feeding, orexins/hypocretins are now acknowledged to play a major role in the control of a wide variety of biological processes, such as sleep, energy expenditure, pain, cardiovascular function and neuroendocrine regulation, a feature that makes them one of the most pleiotropic families of hypothalamic neuropeptides. While the orexigenic effect of orexins is well described, their central effects on energy expenditure and particularly on brown adipose tissue (BAT) thermogenesis are not totally unraveled. Better understanding of these actions and their possible interrelationship with other hypothalamic systems controlling thermogenesis, such as AMP-activated protein kinase (AMPK) and endoplasmic reticulum (ER) stress, will help to clarify the exact role and pathophysiological relevance of these neuropeptides have on energy balance. Highlights: Orexins are pleiotropic regulators affecting several aspects of energy homeostasis. Orexins promote food intake. Orexin neurons sense circulating nutrients. Orexins increase water intake. Orexins induce thermogenesis and brown adipose tissue development.